Impact of the potential evapotranspiration models on drought monitoring - Weiqi Liu; Shaoxiu Ma; Haiyang Xi; Linhao Liang; Kun Feng; Atsushi Tsunekawa (Journal of Hydrology: Regional Studies)
Study region: China Study focus: Potential evapotranspiration (PET) refers to the atmosphere evaporative demand, is a main factor in drought monitoring and prediction. Although over 100 PET models are available, the impact of the model choice on drought monitoring remains unclear. Thus, in this study, 35 typical PET models were selected, aiming to quantify the uncertainty of PET estimation and drought monitoring due to the PET model choice. New hydrological insights for the region: The PET estimated by different PET models were different significantly, with the uncertainty (expressed as standard deviation) of the PET values ranging from 132 to 651 mm/yr. In the arid and humid regions, the PET trends estimated by some models might be opposite. These differences further contributed to the increased uncertainty in drought monitoring. In the arid and semi-arid regions, the meteorological drought (SPEI) and agricultural drought (PDSI) trends, characteristics, and area monitored by some PET models were significantly too high or too low, which resulted in a maximum difference of 2.1-fold in the meteorological drought severity and 2.2-fold in the agricultural drought severity. Drought characteristics monitored by models based on temperature and mass-transfer were always more severe. This study quantified the uncertainty in PET estimation and drought monitoring arising from the PET model choice, emphasizing the importance of selecting a suitable PET model in reducing uncertainty in drought monitoring.